Redefining Dental Practice During and Post-COVID-19 era: A Review (Medico Legal Update, 2020)
The spread of the COVID-19 pandemic has led to widespread concerns internationally and among themembers of the public health community including dental health professionals. The dental health careprofessionals are at higher than usual risk due to the proximity to the patient’s face, direct contact with thebody fluids such as saliva and blood. The objective of this article is to provide an overview of the symptoms,modes of transmission of the COVID-19 infection, triaging of the dental patients, specific recommendationsfor the management of the dental patient, infection control modalities with an emphasis on dental specialties,global outlook on the pandemic by dentists, and implications on the patients and dentists. A literature searchwas performed and articles about the symptoms and modes of transmission of the COVID-19 infection,management of COVID-19 diffusion in dental practice were retrieved. The articles were then reviewedand infection control measures for various dental specialties as well as patient management strategies werealso outlined in the results. The dental team has to implement measures to provide care and treatment to thepatient as well as prevent the spread of the infection.